2019
DOI: 10.1038/s41598-018-36096-7
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression in Circulating Tumor Cells Increases during Radio(chemo)therapy and Indicates Poor Prognosis in Non-small Cell Lung Cancer

Abstract: Preclinical studies demonstrated that radiation up-regulates PD-L1 expression in tumor cells, providing a rationale for combining PD-1/PD-L1 inhibitors with radiation. However this has not been validated in patients with non-small cell lung cancer due to the difficulty to obtain serial biopsies. Measuring PD-L1 expression in circulating tumor cells (CTCs), may allow real-time monitoring of immune activation in tumor. In this study, whole blood from non-metastatic NSCLC patients was collected before, during, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 40 publications
4
89
0
Order By: Relevance
“…Additionally, the post-TACE TIM-3 increase could be the result of immediate HCC antigen release following tumor necrosis that causes excessive and continuous T cell stimulation, leading to gradual overexpression of inhibitory immune receptors such as TIM-3 and PD-1 and finally resulting in further immune exhaustion. Similar observations have been reported in other types of cancer, showing an increase of PD-L1 and TIM-3 expression following chemotherapy-induced tumor necrosis [34,35]. Based on the above, the increase of TIM-3 levels following TACE could be summarized in the "2-hit" hypothesis: (a) the upregulation of TIM-3 expression in order to suppress the inflammation caused by tumor necrosis and (b) the exhaustion of T cells following tumor-antigen overstimulation ( Figure 5).…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, the post-TACE TIM-3 increase could be the result of immediate HCC antigen release following tumor necrosis that causes excessive and continuous T cell stimulation, leading to gradual overexpression of inhibitory immune receptors such as TIM-3 and PD-1 and finally resulting in further immune exhaustion. Similar observations have been reported in other types of cancer, showing an increase of PD-L1 and TIM-3 expression following chemotherapy-induced tumor necrosis [34,35]. Based on the above, the increase of TIM-3 levels following TACE could be summarized in the "2-hit" hypothesis: (a) the upregulation of TIM-3 expression in order to suppress the inflammation caused by tumor necrosis and (b) the exhaustion of T cells following tumor-antigen overstimulation ( Figure 5).…”
Section: Discussionsupporting
confidence: 85%
“…These preliminary results justified closer examination of this pathway and its potential therapeutic role in CSCC. Some studies demonstrated the presence of cell surface PD-1/PD-L1 in human tumors, and this expression has been linked to poor clinical outcomes in a variety of cancers [112][113][114][115][116], including CSCC [117,118]. CSCC has the highest mutational burden of all tumors, and is a good candidate for immunotherapy treatment [21].…”
Section: Immunotherapy In Csccmentioning
confidence: 99%
“…Analysis of PD-L1 expression in CTCs from patients with metastatic lung cancer before and after immunotherapy showed that the overall response to anti-PD-1 immunotherapy was higher in patients with >1.32 CTCs/mL and in those with >50% of PD-L1-positive CTCs [174]. Increased PD-L1 expression on CTCs (≥5% of PD-L1-positive CTCs) in patients with metastatic lung cancer after radiation therapy was associated with poor prognosis [175]. Moreover, PD-L1 overexpression in CSV+ CTCs has been associated with poor prognosis and poor OS in patients with colorectal cancer [176].…”
Section: Ctc Proteomic Analysismentioning
confidence: 99%